Disseminated Juvenile Xanthogranuloma: A Case Report - Najam Us Saher; Palvisha Qadri; Zehra Naseem (Wolters Kluwer Health, 2022)
Introduction:. Histiocytoses are localized or systemic diseases that can broadly be classified into Langerhans cell histiocytosis and non-Langerhans cell histiocytosis. Juvenile Xanthogranuloma (JXG) belongs to the latter group, which occurs in around 0.5% population younger than 5 years, and presents as solitary or multiple lesions. Here, we present a case of disseminated JXG in an infant with the lesions regressing spontaneously. Case presentation:. A 7-month-old boy presented with multiple erythematous nodular lesions over the body excluding limbs for 3 months. Initial laboratory work up was normal. Skin histopathology showed a dermal nodule with sheets of histiocytes exhibiting grooved vesicular nuclei and pale eosinophilic cytoplasm along with touton giant cells. Immunohistochemistry markers further confirmed the diagnosis. Lesions healed completely with symptomatic relief in 1.5 years and no recurrence occurred. Discussion:. Disseminated JXG is a benign childhood disorder that can sometimes be associated with internal organs involvement mainly bones, eyes, and brain. Serious complications may follow in case of extracutaneous spread. Most frequently, JXG follows the occurrence of another neoplastic disorder but can sometimes appear de novo. Skin biopsy is required for the diagnosis and better education of the family. Conclusion:. JXG in infancy is a rarity in South Asia. Therefore, along with the clinical judgment, clinicians must also get histological confirmation in order to manage this disorder successfully. Close surveillance for multiorgan involvement is also required to avoid any irreversible sequalae.